2010
DOI: 10.1103/physrevb.82.054405
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of Fe/MgO based magnetic tunnel junctions with Mg interlayers

Abstract: magnetic tunnel junctions ͑MTJs͒ with Mg interlayers are studied by first-principles calculations. We find that the Mg interlayer is able to preserve the preferential transmission of the majority-spin states with ⌬ 1 symmetry, which dominates the spin-dependent electron transport in MTJs with MgO barrier. A monoatomic layer of Mg at the electrode/barrier interface does not decrease the tunneling magnetoresistance ͑TMR͒ ratio nearly as much as a similar layer of iron oxide. We also find that at a certain Mg thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Incidentally Fe-MgO interfaces have recently attracted a lot of attention since they exhibit a strong transverse magnetic resistance effect. [41][42][43][44][45] In the present work both Fe|MgO and Fe|FeO|MgO interface models were included, the geometries of which are illustrated in Fig. 8.…”
Section: A Ideal Interfacesmentioning
confidence: 99%
“…Incidentally Fe-MgO interfaces have recently attracted a lot of attention since they exhibit a strong transverse magnetic resistance effect. [41][42][43][44][45] In the present work both Fe|MgO and Fe|FeO|MgO interface models were included, the geometries of which are illustrated in Fig. 8.…”
Section: A Ideal Interfacesmentioning
confidence: 99%
“…1 Furthermore, since magnetic tunnel junctions (MTJ), such as a MgO(001) barrier and Fe ferromagnetic (FM) electrodes have high tunnel magnetoresistance, it is expected to be used as novel spintronics devices and magnetic sensors. 2,3 Magnesium oxide (MgO) is an insulator with a band gap of 7.8 eV and has the cubic rock salt structure with a lattice constant of 0.4213 nm, while iron (Fe) is a transition metal and an FM material with a body centered cubic (bcc) structure having a lattice constant of 0.2867 nm. 3,4 Ideally, MgO films can be grown epitaxially on the Fe(001) surface due to a small lattice mismatch of 3.8% on a 45 • in-plane rotation (i.e., Fe(001)[110]//MgO(001)[100]) as well as a lower free energy of the MgO(001) surface (1.1 J/m 2 ) compared to that of the Fe(001) (2.9 J/m 2 ) surface.…”
mentioning
confidence: 99%
“…2,3 Magnesium oxide (MgO) is an insulator with a band gap of 7.8 eV and has the cubic rock salt structure with a lattice constant of 0.4213 nm, while iron (Fe) is a transition metal and an FM material with a body centered cubic (bcc) structure having a lattice constant of 0.2867 nm. 3,4 Ideally, MgO films can be grown epitaxially on the Fe(001) surface due to a small lattice mismatch of 3.8% on a 45 • in-plane rotation (i.e., Fe(001)[110]//MgO(001)[100]) as well as a lower free energy of the MgO(001) surface (1.1 J/m 2 ) compared to that of the Fe(001) (2.9 J/m 2 ) surface. 1,5 Up to now, MgO layers on the Fe(001) surface have been prepared mostly by electron bombardment on MgO sources, but any atomic resolution STM image of MgO layers has not been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is very similar to the minority-d IRS seen in the VCA calculations (Figure 5(b)), and may suggest an even stronger effect of low Co doping in quenching the IRS and leading to a TMR increase. Previous studies have shown the quenching of IRS in a Fe/MgO junction by using an interlayer 10,39,48 , and disorder has been shown to quench surface states in topological insulators 49 . This important result provides new information about the effect of Co concentration on Fe 1−x Co x /MgO IRS and supports the VCA transport results as an accurate representation of the conductance and TMR changes in Fe 1−x Co x /MgO junctions at zero bias.…”
Section: Cpa and Explicit-disordered Model Calculationmentioning
confidence: 99%